Odpowiedzi

2009-11-23T20:23:11+01:00
A) [x+1][x-2]+[x+2][x-1]=x²-2x+x-2=x²-x-2
b) [5k+n][k-2n]-k[4k+n]=5k²-10kn+kn-2n²=3k²-11kn
c) .[4y+3][y-2]-2y[4-2y]=8y²-13y-6
d) nie wiem ;]
e).2[3a²-1]-[a+2][a+2]=5a²+2+4a
2009-11-23T20:24:25+01:00
A.[x+1][x-2]+[x+2][x-1]= x²-2x+x-2+x²-x+2x-2 = 2x²-4
b.[5k+n][k-2n]-k[4k+n]= 5k²-10kn+nk-2n²-4k²-kn=-k²-9kn= -k(k+9n)
c.[4y+3][y-2]-2y[4-2y]=4y²-8y+3y-6 -8y-4y²= -19y-6
d.-[3c-2][c-1]-c[c-2]= -3c²+3c+2c-2-c²+2c= -4c²+7c-2
e.2[3a²-1]-[a+2][a+2]= 6a²-2- a²-2a-2a-4= 5a²-4a-6
f.5x²[x²+1]-[x²-2][x²+3]= 5x⁴+5x² - x⁴-3x²+2x²+6 = 4x⁴+4x²+6

chyba sie nigdzie nie pomylilam..
1 5 1
2009-11-23T20:24:30+01:00
(2)-kwadrat
A)(x(2)-2)+(x(2)-2)
B)(5k(2)-2n(2))-(4k(2)+n)
C)(4y(2)-6)-(4y(2)-4)
D)-(3c(2)=2)-(c(2)-2)
E)(6a(2)-6)-(a(2)+4)
ostatniego nie kumam:-(